Dinamika Dakwah Komunitas Majelis Positif - Daryanti, Ranti (Prophetica : Scientific and Research Journal of Islamic Communication and Broadcasting, 2022)
This study aims to find out about the interaction of da'wah activities, the interdependence of da'wah activities, and the regularity of da'wah activities carried out by the Positive Council community. The research method uses descriptive and qualitative methods as an approach, which describes the development of da'wah activities in the wider Positive Council community. The interaction of the Positive Council community da'wah activities is that each member of the management interacts with each other before and after the process of da'wah activities takes place. Not only offline congregants who can take part in da'wah studies, congregants and social media followers can also follow it via the zoom link provided or can watch the live streaming on the Positive Council youtube, because the study is general in nature. The nature of interdependence in the Positive Council community is closely related to between members, every member of the board who cannot carry out his duties will be assisted by other members.